The generation game: all gain, no pain? Ageing, intergenerational equity and generational accounts - O'Donoghue, Cathal (Statistical and Social Inquiry Society of Ireland, 2001)
This paper tries to quantify the degree of intergenerational redistribution in Irish public expenditure. The development of a large public debt in the space of two decades, its rapid elimination and potential rise again in the next decades due to demographic changes is likely to result in an intergenerational transfer of resources. The paper utilises a database of public expenditure, together with the age incidence distribution of public expenditure to examine the generational net beneficiaries of public spending programs since the foundation of the state in 1921. Demographic and alternative economic scenarios are considered to estimate the lifetime net benefit from public expenditure. Finally the sustainability of current expenditure is examined through the creation of generational accounts.
Read before the Society, 1 February 2001
Keywords: Public expenditure; Intergenerational redistribution; 314.15